Robust intersample crossing of target sets with mixed‐integer linear programming. (14th January 2021) - Afonso, Rubens J. M.; Galvão, Roberto K. H.
Abstract: This note is concerned with the problem of crossing a target set between sample instants under the influence of bounded unknown disturbances. The proposed solution employs mixed‐integer linear programming and is less conservative compared with the standard approach of imposing pointwise‐in‐time constraints at the sample instants.